Pathophysiology of RAGE in inflammatory diseases - Dong, Hanbing; Zhang, Yue; Huang, Yu; Deng, Hui (Frontiers in Immunology, 2022)
The receptor for advanced glycation end products (RAGE) is a non-specific multi-ligand pattern recognition receptor capable of binding to a range of structurally diverse ligands, expressed on a variety of cell types, and performing different functions. The ligand-RAGE axis can trigger a range of signaling events that are associated with diabetes and its complications, neurological disorders, cancer, inflammation and other diseases. Since RAGE is involved in the pathophysiological processes of many diseases, targeting RAGE may be an effective strategy to block RAGE signaling.